Implementasi Pendidikan Karakter Kebangsaan di Pondok Pesantren - Sari, Vita Monika; Indrawadi, Junaidi; Ananda, Azwar; Moeis, Isnarmi (Journal of Civic Education, 2024)
This research was driven by issues related to the national character of students at Darussalam Aur Duri Sumani Islamic Boarding School, where students from diverse regions live and interact daily. The focus of the research is on the implementation of national character education, especially in an environment prone to misunderstandings, indiscipline, and dishonesty. The study aims to describe the form of national character education, the factors influencing its implementation, and its impact on students, focusing on four core values: religiosity, discipline, honesty, and friendship. This qualitative research uses descriptive methods with data collected through observation, interviews, and documentation. The research involves primary and secondary data sources, and purposive sampling for selecting informants, with data validity tested through source triangulation. Data analysis followed stages of reduction, presentation, and conclusion. Findings indicate that the pesantren addresses character issues by implementing habits that promote these values, including religious practices, discipline, honesty, and friendship. The factors influencing this implementation are the objectives of the pesantren, its learning environment, and the students' conditions. The impact of this education is evident in the development of positive personalities, enhanced kinship, and improved politeness in language. Limitations of this research include its focus on only one pesantren, limiting its generalizability, and the lack of exploration into external factors influencing character education.